Un cuento interactivo digital en el desarrollo de la lectoescritura para niños de preparatoria - Monar Naranjo, Lady Michelle (2024)
Research on digital interactive stories is crucial due to its potential to transform educational process. These tools offer active and engaging learning experiences that engage children in a meaningful way, stimulating the development of key reading and writing skills in a more effective and customized way. They encourage a love of reading from an early age and prepare children for a constantly evolving digital world. This research promotes literacy using an interactive digital story. To achieve the objective, the story was structured by adapting literacy activities from various web pages. This story was implemented with high school children from “The Oxford Garden’s School” Educational Unit. Also, their satisfaction level of the digital interactive story was evaluated. The research is characterized by a pre-experimental methodology, which allowed the phenomenon to be described and analyzed in its real context, without the manipulation of independent variables. The qualitative approach facilitated a detailed description of the children’s interaction with the digital story. Observation techniques were used and complemented by the use of a field diary and focus groups. They allowed a depth analysis of the digital interactive story impact in order to promote students’ literacy. The relevance of this research in the educational field is significant, since it represents an innovative convergence between traditional narrative and modern technology. Digital and interactive stories offer a unique opportunity to promote active and personalized learning, stimulating the development of reading and writing skills in an attractive and effective way.